Beyond Emergency Response: From Event-Based Regulations to System-Based Regulation in the Governance of Post-Disaster Health Crisis Management in Aceh - Aisyah, Defani Putri; Fitriani, Diana Nopiar; Salsabilah, Mauli; Mujahid Maolani, Fakhri (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2026)
Employee performance plays a critical role in achieving organizational objectives, particularly in organizations dominated by Generation Z employees, who exhibit distinct work characteristics compared to previous generations. This study aims to examine the influence of servant leadership, participative leadership, and quality of work life on the performance of Generation Z employees. A quantitative approach was employed using a survey method. The sample consisted of 56 Generation Z employees, comprising 50 females and 6 males, with the majority aged under 25 years. Data were collected through online questionnaires and analyzed using multiple linear regression analysis. The findings reveal that servant leadership has a significant positive effect on employee performance. In contrast, participative leadership and quality of work life do not show significant partial effects. However, the three variables collectively exert a significant influence on employee performance. These results highlight the critical role of service-oriented leadership in enhancing the performance of Generation Z employees, suggesting that leadership approaches emphasizing empathy, support, and employee development are particularly relevant for this cohort.